Prevalence of malnutrition in medical and surgical gastrointestinal outpatients. (February 2020) - Kamperidis, N.; Tesser, L.; Wolfson, P.; Toms, C.; Katechia, K.; Robinson, D.; Nightingale, J.
Summary: Background: UK NICE guidelines, state that patients attending an outpatient clinic for the first time, should be screened for malnutrition. Aims: To determine the prevalence of malnutrition in the medical and surgical gastroenterology outpatient department (OPD) using body mass index (BMI) and % weight loss (%WL) and to assess the physicians'/surgeons' response to malnutrition being detected. Methods: The BMI and the %WL were determined for every patient over a 2 week period before the clinician saw the patient. The BMI and %WL were scored as in the Malnutrition Universal Screening Tool (MUST). Results: 605 patients (316 females) of mean age 54 years were included. 150 (25%) were new patients. 519 (86%) had a normal BMI and %WL. 86 (14%) had a BMI <20 kg/m 2 or had 5% WL. 61 (10%) were in MUST "medium risk" and 25 (4%) were in MUST "high risk" of malnutrition. 15 (60%) of the "high risk" patients were under the care of or had been referred to a dietitian compared to 19 (28%) of "medium risk" patients. The prevalence of malnutrition was independent of sex, age, history of previous surgery or underlying comorbidities. There was no difference in the prevalence of malnutrition between new and follow up patients. Malnutrition was more common in patients with IBD (38, 18%) vs non-IBD (48, 12%) and patients with cancer (11, 25%) vs non cancer (75, 13%) (p < 0.05). Conclusions: The prevalence of malnutrition in medical and surgical gastrointestinal outpatients was 14%. IBD and cancer patients had the highest prevalence. Most patients with malnutrition (52, 61%) were not being seen by a dietitian.